Selective dopaminergic vulnerability in Parkinson’s disease: new insights into the role of DAT - Harraz, Maged M. (Frontiers in Neuroscience, 2023)
One of the hallmarks of Parkinson’s disease (PD) is the progressive loss of dopaminergic neurons and associated dopamine depletion. Several mechanisms, previously considered in isolation, have been proposed to contribute to the pathophysiology of dopaminergic degeneration: dopamine oxidation-mediated neurotoxicity, high dopamine transporter (DAT) expression density per neuron, and autophagy-lysosome pathway (ALP) dysfunction. However, the interrelationships among these mechanisms remained unclear. Our recent research bridges this gap, recognizing autophagy as a novel dopamine homeostasis regulator, unifying these concepts. I propose that autophagy modulates dopamine reuptake by selectively degrading DAT. In PD, ALP dysfunction could increase DAT density per neuron, and enhance dopamine reuptake, oxidation, and neurotoxicity, potentially contributing to the progressive loss of dopaminergic neurons. This integrated understanding may provide a more comprehensive view of aspects of PD pathophysiology and opens new avenues for therapeutic interventions.